2022
DOI: 10.1155/2022/7796700
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Status and Clinical Outcomes after Mechanical Thrombectomy in Patients with Anterior Circulation Occlusion

Abstract: Background. Successful mechanical thrombectomy (MT) requires reliable, noninvasive selection criteria. We aimed to investigate the association of collateral status and clinical outcomes after MT in patients with ischemic stroke due to anterior circulation occlusion. Methods. 109 patients with poor collaterals and 110 aged, sex-matched patients with good collaterals were enrolled in the study. Collateral circulation was estimated by the CT angiography with a 0–3 scale. The collateral status was categorized as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Consistent with their hypothesis, the researchers discovered that patients who underwent endovascular therapy (EVT) for anterior circulation LVO caused by cervical large-artery atherosclerosis displayed more extensive cerebral collateral circulation and better functional outcomes at 90 days compared to those with cardioembolic stroke. However, no statistically significant differences were observed in terms of functional independence (mRS score of 0-2) or mortality between the two groups [60,61].…”
Section: Discussionmentioning
confidence: 75%
“…Consistent with their hypothesis, the researchers discovered that patients who underwent endovascular therapy (EVT) for anterior circulation LVO caused by cervical large-artery atherosclerosis displayed more extensive cerebral collateral circulation and better functional outcomes at 90 days compared to those with cardioembolic stroke. However, no statistically significant differences were observed in terms of functional independence (mRS score of 0-2) or mortality between the two groups [60,61].…”
Section: Discussionmentioning
confidence: 75%
“…First, patients who present with a more severe stroke may have a larger and/or more invasive blood clot that is more challenging to remove, resulting in less complete recanalization of the occluded vessel(s) 30,31 . Second, higher admission NIHSS is associated with worse collateral status, 32–34 which in turn is associated with less successful reperfusion following endovascular treatment 35,36 . Third, patients with more severe stroke symptoms are more likely to already have extensive and/or irreversible ischemic brain damage than those with milder symptoms, whether due to the severity of the clot or a delay in their evaluation, limiting the amount of reperfusion that can be achieved through MT.…”
Section: Discussionmentioning
confidence: 99%
“…26 Xu et al reported that beter collateral status was associated with increased rate of good clinical outcome and lower mortality after MT. 27 However, these studies included AIS patients in the early time window. A recent study evaluated the effect of collaterals in AIS patients treated within and after six hours, and authors reprted that presence of good collaterals had association with better clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%